Water, sanitation and hygiene practices among adult women in a rural area of Kolar district, South India: a community based survey - Ramya, Nagesh; Reddy, Mahendra M.; Kamath, Prasanna B. T. (International Journal Of Community Medicine And Public Health, 2020)
Background: In developing countries, monitoring and assessing the change in water, sanitation and hygiene (WaSH) practices still remains to be a challenge especially in rural areas. The objective of the study was to assess the practices related to WaSH and factors associated with good WaSH practices among rural adult women belonging to Kolar district of Karnataka, India. Methods: A community based cross-sectional study was conducted in a village of Kolar district during July - October 2018. Socio-demographic details and water related characteristics were collected from an adult female of the household using a pre-tested semi-structured interview schedule. The WaSH practices were captured using a set of 15 questions designed after a thorough literature search. WaSH score was categorised into good practice or not based on cut-off value of WaSH score ≥third quartile. Results: Out of total 108 households enlisted a total of 82 households (76%) comprising of 464 individuals was surveyed. The number of people reporting good WaSH practices was 40 (48.8%). Multivariable logistic regression model containing all independent variables studied showed statistical significance with respect to family type alone (nuclear family having statistically significance compared to three generation family; Odds ratio (95% Confidence Interval) =11.9 (2.7-52.0). Conclusions: One in two women had good WaSH practice and among the individual components use of soap after defecation was practiced in less than one in ten women under study.